Development of Contextual-Based Nahwu Teaching Materials for VII Class at MTsN 3 Jombang - Rina Dian Rahmawati; Arinatus Sa'diyah (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This research is motivated by the absence of specific teaching materials based on contextual Nahwu material. This study aims to determine (1) the design of the arrangement, (2) the quality of the teaching materials and (3) the students' responses to the contextual-based nahwu teaching materials at MTsN 3 Jombang. This type of research is research and development or Research and Development (R&D) which refers to the ADDIE model. The research and development steps in this study were analyzed by means of a preliminary study of product design and product evaluation. The research instrument with a questionnaire scale with 4 categories arranged in the form of checklists and learning outcomes tests. The results showed that: (1) the contextual-based design of nahwu teaching materials at MTsN 3 Jombang was in the very feasible category (85%), (2) the quality of the contextual-based nahwu teaching materials at MTsN 3 Jombang which was assessed by material substance experts was at Very feasible category (83%) and (3) the response of students is very positive in assessing teaching materials strongly agree (83%), and the data on student learning outcomes tests after using teaching materials are in the very good category. Thus the contextual-based nahwu teaching material can be used in the learning process.